Evaluasi Program Literasi Al-Qur’an di SMA Negeri 6 Bulukumba (Studi Evaluasi Model Context, Input, Process, dan Product) - Rostina; Ilham Muchtar; Abd. Rahman Getteng (Risalah, Jurnal Pendidikan dan Studi Islam, 2022)
This study aims to describe the results of the implementation of the Koran literacy program at SMA Negeri 6 Bulukumba with an evaluation study of the CIPP model, namely Context, Input, Process, and Product. This evaluative research uses a qualitative descriptive method. The results of the research show that: 1) The aim of implementing the Koran literacy program is in accordance with the needs of students and schools, and for the development of the Koran literacy program SMA Negeri 6 has collaborated with related institutions and agencies. 2) Evaluation of the input implementation of the literacy program in the form of activity schedule stages, understanding of teachers and students in program management, qualifications of TLA members, availability of infrastructure, implemented well although it has to be increased in human resources competency stage of accompanying teachers, utilization of facilities, planning of programming, rules for funding training and program development. 3) The process of implementing the Al-Qur'an literacy program, time and place has changed due to the Covid-19 pandemic, the role of program partners and school principal monitoring supervision has been very good even though it has not yet touched program development funding. 4) Product evaluation of the implementation of the Koran literacy program that was implemented showed the success of the program in terms of target and outcome compatibility, changes in students' interest in reading the Koran intensively, increasing learning outcomes in the rules of reading the Koran and student achievement in the religious field, program benefits for schools and program reporting. This program must be continued and can be applied elsewhere.